Three centuries of corporate governance in the UK - John D. Turner (Queen's University Centre for Economic History (QUCEH), 2024)
As articulated by Adam Smith, one of the central issues facing companies is that managers will not run the business in the interests of its owners and will misuse resources. This ultimately has a detrimental consequence for the wealth of the nation. This survey reviews the nature and evolution of the corporate governance of UK public companies over the past 300 years. It makes two principal arguments. First, because the separation of ownership and control was one of the rationales for the introduction of the corporate form, we should not be surprised that corporate ownership has generally been diffuse. Second, over time, the way in which owners ensure that managers act in their interests has gradually changed from a system in which shareholders monitored and exercised voice to one where there was more reliance on external forces and exiting ownership.
Keywords: G30; G34; K22; N23; N24; N83; N83; 330; Corporate governance; shareholders; ownership; control; agency costs; UK